A comparative study on histopathological features of duodenum, jejunum, and ileum from broiler chicken with avian pathogenic Escherichia coli infection - F. N. A. E. P. Dameanti; A. O. Dacosta; S. L. Adrenalin; M. Fatmawati; F. S. Permata; H. P. Siswanto; T. Ariyanti (Journal of the Indonesian Tropical Animal Agriculture, 2023)
Avian colibacillosis is a high-prevalence chicken farm disease caused by avian pathogen-ic Escherichia coli (APEC). It is necessary to identify and look up to the bacterial activity to stave off a decline in chicken performance. This study aimed to identify and determine the pathogenetic activity of APEC within broiler chickens on the duodenum, jejunum, and ileum histopathology comparison. The samples were collected from a total of 40 broilers, obtained from a highest-colibacillosis historical chicken house, identified with bacterial isolation swab-technique, and analyzed with nonparametric statistical lesions scoring. The identification result showed 82.5% E. coli with a 62.5% APEC con-firmed. The histopathological feature showed a significant difference (p<0.05), where the jejunum ap-peared to encounter the most significant damage compared to the duodenum and ileum. Thus, it is con-cluded that APEC field infection varies in characteristics and pathogenicity, which affects intestinal organs based on the histology changes, mainly in the jejunum part of the intestine.